Penegakan Hukum bagi Pelaku Tindak Pidana Transaksi Jual Beli Online E-Commerce - Affianto Affianto; Muhammad Ishlahuddin (AHKAM, 2025)
The limited body of research on law enforcement against perpetrators of fraud in online buying and selling transactions forms the background of this study, considering its significant impact on public trust within Indonesia’s e-commerce ecosystem. This study aims to analyze the application of law to online fraud perpetrators and identify the challenges and strategies for overcoming them. The research employs a normative juridical method with statutory and conceptual approaches. Data were obtained through a literature review of legal regulations, scholarly legal texts, and analyses of relevant cases, and were then qualitatively analyzed. The findings indicate that perpetrators of fraud in online transactions may be prosecuted under Article 378 of the Indonesian Criminal Code (KUHP), Article 62(1) of Law No. 8 of 1999 on Consumer Protection, and Article 28(1) in conjunction with Article 45(2) of Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law). However, the enforcement of these laws still faces considerable obstacles, including difficulties in digital evidence collection, tracking perpetrators' identities, and low legal literacy among the public. The study concludes by emphasizing the need to strengthen the cyber legal framework and optimize the role of the ITE Law as a relevant legal instrument. It recommends fostering synergy between law enforcement agencies, digital stakeholders, and the public to build a secure and equitable e-commerce ecosystem. The implications of this study not only enrich the literature on cyber law but also offer strategic insights for policy development on technology-based consumer protection and the advancement of a legal enforcement system that is adaptive to the dynamics of digital transactions.